The âPamaliâ of Wakatobi Bajo and Its Role for Marine Conservation - Baskara, Benny; Astuti, Oce (Journal of Indonesian Coral Reefs, 2011)
The Bajo people are known as the sea people, because they live and depend on the sea for their livelihood. As in any other cultures, the Bajo people also have their own ethical system, which prevails as a ruling guide for their life. The ethical system of the Bajo people is called âPamaliâÂ. This Pamali system is a kind of taboo system, which contains forbidden things that should not to be done. The example of things in Pamali concerned with the sea include: the disposal of waste in the sea, such as lemon peels, sFiges, and any other unused things, including spitting to the sea. Another example is that it is forbidden to catch small fishes and consume them before they reach harvestable size. Because the Bajo people are the sea people, they should keep and maintain the sea as their life environment. The Pamali system is the way for the Bajo people to keep and maintain the sustainability of their life in the sea. The overall program and policy on natural conservation in a wider scope in Indonesia should consider the local genius of the indigenous people, such as local values, wisdoms, and customs, which also play a significant role in maintaining the sustainability of their natural environment, in this case is the Pamali system of the Bajo people.